Marquis de Sade: against the sex-gender determinism and the closed heterosexuality - Solano Fallas, Andrés (2017)
This paper analyses the philosophical position of the Marquis de Sade’s selected opera, on sexual diversity. In a first moment, it will be study the critic he carries on to the conception of sex-gender determinism. In a second moment, it will be examine his critic to the conception of an obligatory and normative heterosexuality. In each moment, it is explain the philosophical assumptions that serve him as basis. This two critics of Sade, allows conceiving how in his literary opera and thought the naturalness of sexual diversity it is explained and possible. It should be noted that this paper is from an analytical approach.